Prevalence of thiamine deficiency in older hospitalized patients - Pourhassan M (Dove Medical Press, 2018)
Maryam Pourhassan,1 Hans Konrad Biesalski,2 Bjoern Angersbach,1 Gero Lueg,1 Christiane Klimek,1 Rainer Wirth1 1Department of Geriatric Medicine, Marien Hospital Herne, Ruhr-University Bochum, Herne, Germany; 2Institute of Biological Chemistry and Nutritional Science, University of Hohenheim, Stuttgart, Germany Purpose: Despite some reports of high prevalence of thiamine deficiency in elderly people, the reported prevalence is controversial mainly due to the methods used in assessing thiamin concentrations. In this study, we sought to investigate the prevalence of vitamin B1 deficiency, using the high-performance liquid chromatography (HPLC) method, among older hospitalized patients.Patients and methods: This cross-sectional study retrospectively analyzed the results of routine measurements of vitamin B1 of 238 older patients who were consecutively hospitalized to a geriatric acute care ward. Whole blood vitamin B1 concentrations were measured using the HPLC method at hospital admission, and the whole blood vitamin B1 level of <20 ng/mL was considered as deficiency.Results: Of 238 patients, with a mean age of 82.1±7.1 years, 63% of patients were women. In total, the mean whole blood vitamin B1 level was 66.1±24.8 ng/mL (range 29.5–215 ng/mL), indicating no vitamin B1 deficiency in the entire population. In addition, no significant differences in the mean whole blood vitamin B1 concentrations between sexes were observed (P=0.356).Conclusion: This study indicates that the mean whole blood vitamin B1 concentrations using the HPLC method were within the normal range in older hospitalized patients suggesting that thiamine deficiency appears to be rather uncommon among these patients. Keywords: vitamin B1, thiamine deficiency, older people